Meloidogyne spp. Penyebab Puru Akar Tanaman Seledri di Kelurahan Landasan Ulin Utara, Kota Banjarbaru - Fitriyanti, Dewi; Aidawati, Noor (Jurnal Fitopatologi Indonesia, 2022)
Meloidogyne spp. as The Causal Agent of Root Knot on Celery in Landasan Ulin Utara, Banjarbaru Root knot disease caused by root knot nematodes (RKN) or Meloidogyne spp. often cause a serious problem for the celery farmers in vegetable centers in the sub-district of Landasan Ulin Utara, Banjarbaru. However, until now there is no report regarding the species of Meloidogyne that causes this disease in the Landasan Ulin Utara. This study aimed to identify the species of Meloidogyne on celery through the morphological observation of the perineal pattern of female RKN. Celery plants infected by Meloidogyne spp. were taken by a purposive method based on the typical root symptoms from three locations in sub-district of Landasan Ulin Utara namely Kurnia, Sukamara, and Sukamaju Ujung villages. Based on the characters of perineal pattern, three species of nematodes was identified, i.e. Meloidogyne arenaria, M. incognita, and M. javanica were found in those three sampling sites.